2014
DOI: 10.1002/2014gl061448
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen site analysis of hydrous ringwoodite in mantle transition zone by pulsed neutron diffraction

Abstract: Hydrogen site positions and occupancies in the crystal structure of synthetic hydrous ringwoodite have been determined for the first time by high-resolution neutron powder diffraction conducted at the pulsed neutron source at Japan Proton Accelerator Research Complex (J-PARC). It is demonstrated that hydrogen exchanges not only with Mg or Fe but also with Si cations to form hydroxyl and hydrogen bonding, both within the relevant octahedra or tetrahedra created by their surrounding oxygen anions. The hydrated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
4
29
2
Order By: Relevance
“…Matveev et al 2001;Lemaire et al, 2004), which is consistent with that in hydrous ringwoodite (e.g. Ye et al, 2012;Purevjav et al, 2014). (3) Combinations of Mg 2+ , Si 4+ , Ti 4+ , as well as trivalent-cation vacancies (e.g.…”
Section: Olivinesupporting
confidence: 56%
See 1 more Smart Citation
“…Matveev et al 2001;Lemaire et al, 2004), which is consistent with that in hydrous ringwoodite (e.g. Ye et al, 2012;Purevjav et al, 2014). (3) Combinations of Mg 2+ , Si 4+ , Ti 4+ , as well as trivalent-cation vacancies (e.g.…”
Section: Olivinesupporting
confidence: 56%
“…Therefore it can be concluded that Mg 2+ =2H + substitution is the dominant hydration mechanism when C H 2 O <2 wt.%, while Si 4+ =4H + also become important when C H 2 O >2 wt.%. This hydration mechanism in hydrous ringwoodite is different from that in hydrous wadsleyite, and supported by following neutron diffraction experiment (Purevjav et al, 2014).…”
Section: Ringwooditementioning
confidence: 66%
“…This f-TiZr alloy was successfully applied to experiments involving the generation of high static pressures, which requires the extensive deformation of the hard metal. In addition, the f-TiZr alloy was also used to fabricate a thin-walled micro-sample container, which enabled us to obtain a background-free NPD pattern with a pulsed-neutron source [24,25]. The successful application of the f-TiZr alloy has demonstrated that forged TiZr products may play a complementary role in future neutron scattering research.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1a shows a cross section of the cell coupled with 8 mm TEL, which was used for the phase E, wadsleyite, and ringwoodite synthesis. This cell design was established in our previous work for mass production of fully deuterated ringwoodite powder (Purevjav et al 2014a). In the present study, the same gold capsule of 4 mm in diameter and 5 mm in length in this cell, with ~50 mm 3 in sample volume, was successfully used for the significantly longer heating durations required for single-crystal growth.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…4a), it was confirmed that these deuterated phase E crystals are suitable for structure refinement or other studies that require chemical and isotopic homogeneity within their entire crystal volumes. The uniform hydrogen isotope abundance of 14% in all measured crystals indicates that hydrogen was contaminated into the crystals from sources outside of the capsule such as hydrogen released from an MgO sleeve or MgO-Cr 2 O 3 pressure medium despite calcination at 1000 °C immediately prior to the cell construction and compression, because isotope abundance of hydrogen was less than 1% in the deuterated starting material in the capsule (Purevjav et al 2014a). We are now conducting a structure refinement study of phase E from the TOF-NPD pattern of the PE02 sample having known hydrogen isotope abundance in this study ).…”
Section: Dhms Phase E Crystalsmentioning
confidence: 99%